When expansion stalls: an extension to the concept of range pinning in ecology. Issue 2 (28th December 2021) - Morel‐Journel, Thibaut; Haond, Marjorie; Lamy, Laurent; Muru, David; Roques, Lionel; Mailleret, Ludovic; Vercken, Elodie
Abstract : Identifying the factors modulating range expansion is essential to accurately predict changes in the spatial distribution of populations. By preventing population growth after dispersal, Allee effects can lead to front stops in discrete space, called 'pinning' if permanent. However, other mechanisms, such as positive density‐dependent dispersal, have also been shown to affect the rate of range expansion and generate discrete‐space front stops, albeit temporarily. In this study, we investigated the stability of the front stops generated by such mechanisms in relation to the carrying capacity of the environment. To this end, we performed artificial range expansions in discrete space using stochastic simulations and microcosm experiments. Simulation results confirmed that density‐dependent dispersal alone can generate sustained front stops, albeit for a limited range of carrying capacities. We also highlighted the synergy between Allee effects and density‐dependent dispersal on pinning emergence. Experimental results, obtained using a model species known to exhibit density‐dependent dispersal, but without Allee effects, confirmed the model results. Furthermore, our study raises the issue of carefully considering the conditions for pinning stability, in a stochastic context and depending on the time‐scale considered.